(untitled) (Globalization and Business, 2023)
The article assesses the perspectives of achieving sustainable development goals and implementation of sustainable business models in Post-Covid era. Challenges created by the novel corona virus (Covid-19) pandemic have been analyzed in the context of sustainable development using desk research method and qualitative content analysis. Pandemic crisis gradually develops into a "triple wave" crisis: 1) pandemic shock and public health crisis; 2) a stronger shock of economic global mega-recession, 3) an even more powerful ecological crisis caused by climate change and declining biodiversity might be emerge. According to the Organization for Economic Cooperation and Development (OECD) the total "lockdown" of economy caused by pandemic leads to a reduction of almost one-third of the gross domestic product (GDP) in the world's leading economies. Each month of economic “lockdown” causes a 2% loss of annual GDP. If some sectors of the economy can only be partially "locked down", then the initial reduction in GDP in most leading economies will be 20% -25%. According to the World Bank pandemic and “lockdown” of world’s leading economies could push to extreme poverty more than 60 million people and eliminate all the results achieved in the past years in poverty eradication. Achieving sustainable development goals and implementation of sustainable business models might stay away from attention. In the future the frequency of pandemics will increase if humanity does not stop destroying nature. It is known that among mammals and water birds 1.7 million unknown viruses are inhabited that could be transmitted to human beings. Unrestrained deforestation, agrarian expansion, and infrastructure creation bring humans closer to these mammals and birds. The pandemic situation is causing changes in the socio-political context. There are signs of politicization in the fight against corona virus-phenomena called infodemia and covidism. We observe excessive bans introduced by governments, restrictions on international trade, calls for protectionism, propaganda of nationalism, attempts to introduce authoritarianism, violation of fundamental human rights, attempts to spread mass fear and hysteria through the media. The article evaluates two alternative scenarios for socio-economic development of post-pandemic period. In the current global mega-recession markets are changing radically, in the face of growing uncertainty firms are trying to adapt to new conditions. On the front line the "big" state appears, which acts as a leader in dealing with the pandemic and restoring the economy. In the Post-Covid era, a "new normal" situation is expected to emerge, which can develop in two possible directions. Undesirable direction is reduction of public services, ecological crisis caused by climate change, nationalism, autocracy. The preferred direction of development is more internationalization, new paradigms of business management, investments oriented on sustainable development, implementation of sustainable business modes, a new green deal and democracy. In order to reduce the risks of future pandemics, in the Post-Covid period a stimulus policy should be concentrated on the protection of human life and healthcare, provision of livelihoods, nature conservation and protection.